2006
DOI: 10.1007/s10151-006-0297-7
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive resection for colorectal cancer: perioperative and medium-term results in an unselected patient group at a single institution

Abstract: Minimally invasive laparoscopic resection for colorectal cancer enables an oncologically adequate resection with complication and survival rates that are no worse than are to be expected after traditional open surgery. Locally advanced tumor and bowel distension are the most frequent reasons for conversion to open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…9 The results obtained in our unit were similar if not even better than those published in other studies and mostly obtained in referral university centers. As references, COST 10 and CLASSIC 5 study, for their laparoscopic arm had Ͻ1%, 21%, and 4%, 13% as mortality and morbidity rates, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…9 The results obtained in our unit were similar if not even better than those published in other studies and mostly obtained in referral university centers. As references, COST 10 and CLASSIC 5 study, for their laparoscopic arm had Ͻ1%, 21%, and 4%, 13% as mortality and morbidity rates, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, there had been individual reports of so-called port-site metastases. However, a number of recently published comparative studies have impressively shown that, in the hands of experienced surgeons operating in compliance with the requirements of oncological resections, laparoscopic procedures achieve comparable results in terms of survival and recurrence rates [1][2][3][4][5]13].…”
Section: Discussionmentioning
confidence: 99%
“…The top priority of the surgical management of patients with malignant disease is always to guarantee the oncological radicality of the operation. Numerous studies have shown that in terms of survival and recurrence rates laparoscopic techniques provide results comparable with those achievable with open surgery [1][2][3][4][5]. In the hands of an appropriately experienced surgeon, therefore, laparoscopic or laparoscopically assisted resection of colorectal carcinomas can be recommended as an alternative to the open procedure that offers the benefits of minimally invasive surgery while not compromising radicality-at least within the framework of prospective studies [1][2][3].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The surgical techniques used were similar to those described by other authors in all the principal phases and according to the standard laparoscopic procedures for colon resection (right and left sides) [8,9]. In all cases, a mechanical bowel preparation was completed.…”
Section: Technical Aspectsmentioning
confidence: 99%